Evaluation of teaching on violence at a Faculty of Medicine - Garmendia Lorena, Fausto (2013)
Objectives: To determine changes and innovations in teaching on violence at the Faculty of Medicine, Universidad Nacional Mayor de San Marcos (UNMSM), Lima, Peru, from 2005 until academic year 2011, time in which diverse coordinations with academic and faculty authorities were done to improve teaching on violence. Design: Descriptive, transversal and analytical study of syllabi. Institution: Faculty of Medicine, UNMSM, Lima, Peru. Material: Syllabi. Methodology: In year 2012, 79 selected syllabi corresponding to academic year 2011 of the five schools of the Faculty of Medicine were studied. Main outcome measures: Changes and innovations in violence contents. Results: There was increment in contents on teaching of violence in selected syllabi from 30/81 (37%) in year 2005 to 58/79 (73.4%) in year 2011. In the School of Medicine increase was from 47% to 89.4%, in the School of Midwifery from 45% to 85%, in the School of Nursery from 40.6% to 72.7%, in the School of Medical Technology from 31.5% to 47.3%, and in the School of Nutrition from 10% to 50%. Conclusions: Teaching on violence has improved from year 2005 to 2011 at the Faculty of Medicine; therefore professionals trained by the Faculty of Medicine will have better skills to attend violence victims and will contribute to the solution of this public health problem.